1992
DOI: 10.1212/wnl.42.1.138
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative MRI study of vascular dementia

Abstract: We studied the MRI and clinical factors associated with dementia following stroke by quantifying ventricle-to-brain ratio (VBR), anatomic region of infarction, and cortical, subcortical, and white matter areas of infarction in 24 stroke patients with dementia and 29 nondemented stroke patients. The factors that most strongly correlated with dementia were total white matter lesion (WML) area, left WML, VBR, right WML, age, left cortical infarction area, left parietal infarction area, and total infarction area. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
92
1
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(100 citation statements)
references
References 0 publications
6
92
1
1
Order By: Relevance
“…Our data also confirm the association between dementia and ventricular enlargement, noted by other investigators studying heterogeneous samples of large-and small-artery type VaD. 3,14,15 MRI and computerized segmentation methods used in the current study enable demonstration of a stronger association between dementia in SIVD and specifically neocortical as well as hippocampal atrophy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data also confirm the association between dementia and ventricular enlargement, noted by other investigators studying heterogeneous samples of large-and small-artery type VaD. 3,14,15 MRI and computerized segmentation methods used in the current study enable demonstration of a stronger association between dementia in SIVD and specifically neocortical as well as hippocampal atrophy.…”
Section: Discussionsupporting
confidence: 91%
“…Atrophy of the hippocampus and medial temporal lobe, anatomic regions highly susceptible to neurofibrillary degeneration, are characteristically observed in AD. [10][11][12] Previous investigators have correlated dementia in SIVD with the severity of ventricular enlargement, 3,[13][14][15] white matter lesions, 14,[16][17][18] cerebral hypoperfusion, 13,18,19 and number, but not necessarily volume, of lacunes. 3,16,19 One group has noted the presence of hippocampal atrophy in VaD, as well as AD.…”
mentioning
confidence: 99%
“…Stroke severity and level of education are well-known risk factors. 9 -11,13,16 Similarly, an association between the extent of white matter lesions and PSDE has been reported, 10,33 although not consistently. 15 For instance, Miyao et al 34 have demonstrated that, after the first lacunar infarction, the prevalence of dementia is higher in patients with leukoaraiosis.…”
Section: Discussionmentioning
confidence: 97%
“…The left-sided predominance of lesions in demented patients with large-vessel stroke in territories of the anterior and posterior cerebral arteries has been repeatedly demonstrated [20]. Other risk factors include current smoking, lower blood pressure, orthostatic hypotension, and larger periventricular white matter ischemic lesions by brain CT or MRI [21, 22]. Hypoxic and ischemic complications of acute stroke (e.g., seizures, cardiac arrhythmias, aspiration pneumonia, etc.)…”
Section: Risk Factors For Post-stroke Vadmentioning
confidence: 99%